2019
DOI: 10.1002/mnfr.201800978
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus sakei Alleviates High‐Fat‐Diet‐Induced Obesity and Anxiety in Mice by Inducing AMPK Activation and SIRT1 Expression and Inhibiting Gut Microbiota‐Mediated NF‐κB Activation

Abstract: Scope Long‐term feeding of a high‐fat diet (HFD) causes gastrointestinal inflammation and gut microbiota disturbance, leading to the increased occurrence of obesity and anxiety. In the present study, the effects of heat‐labile Lactobacillus sakei OK67, tyndallized OK67 (tOK67), and heat‐stable Lactobacillus sakei PK16 on HFD‐induced obesity and anxiety in mice are examined. Methods and results Obesity is induced in mice by feeding with HFD. Oral administration of live OK67, tOK67, or PK16 reduces HFD‐induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 55 publications
(88 reference statements)
2
52
0
1
Order By: Relevance
“…To decide the dosage of these bacteria in the in vivo experiment, K1 at doses of 1 × 10 7 , 1 × 10 8 , and 1 × 10 9 CFU/mouse/day was orally gavaged for 5 days in mice and depression-like behaviors were measured in the EPM task, as the previously reported (44). NK41 at doses of 1 × 10 8 and 1 × 10 9 CFU/mouse/day was orally gavaged for 5 days in K1-treated mice and behaviors were measured in the Y-maze and elevated plus maze (EPM) tasks, as previously reported (10).…”
Section: Culture Of Escherichia Coli K1 and Lactobacillus Mucosae Nk41mentioning
confidence: 99%
See 1 more Smart Citation
“…To decide the dosage of these bacteria in the in vivo experiment, K1 at doses of 1 × 10 7 , 1 × 10 8 , and 1 × 10 9 CFU/mouse/day was orally gavaged for 5 days in mice and depression-like behaviors were measured in the EPM task, as the previously reported (44). NK41 at doses of 1 × 10 8 and 1 × 10 9 CFU/mouse/day was orally gavaged for 5 days in K1-treated mice and behaviors were measured in the Y-maze and elevated plus maze (EPM) tasks, as previously reported (10).…”
Section: Culture Of Escherichia Coli K1 and Lactobacillus Mucosae Nk41mentioning
confidence: 99%
“…To evaluate the anti-depressive effects of gut bacteria in mice, the EPM task was performed in the plus-maze apparatus (consisting of two open [30 × 7 cm] and two enclosed arms [30 × 7 cm] with 20-cm-high walls extending from a central platform [7 × 7 cm] on a single central support to a height of 60 cm above the floor) for 5 min according to the method of Jang et al (44). The tail suspension (TS) task was measured according to the method of Dunn and Swiergiel (46).…”
Section: Cognitive and Depressive Behavioral Tasksmentioning
confidence: 99%
“…Various methods have been implemented in overweight or obesity management and, in the last two decades, more and more attention has been paid to the role played by gut microbiota in the development and treatment of obesity [6,7]. It has been found that obesity is generally associated with an alteration in the composition of gut microbiota and, overall, people with obesity have less microbial diversity compared with lean people [6,8]. Furthermore, a large body of evidence has revealed the correlations between certain microbial communities and the occurrence of obesity, although the exact mechanisms remain obscure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics efficacy in suppressing high-fat diet impacts on the gut microbiome and gut permeability are mediated via the upregulation of SIRT1 in intestinal epithelial cells and the liver [54]. SIRT1 knockout, specifically in intestinal epithelial cells, highlights the importance of SIRT1 in the regulation of gut dysbiosis and inflammatory activity [55].…”
Section: Gut Sirtuins and Alzheimer's Diseasementioning
confidence: 99%